EFEKTIVITAS KELAMBU BERINSEKTISIDA DALAM PENGENDALIAN VEKTOR MALARIA DI INDONESIA - Rizki Nurmaliani; Maya Arisanti (Balai Penelitian dan Pengembangan Kesehatan Baturaja, 2021)
Malaria is still a health problem in several parts of Indonesia. National malaria elimination is targeted at 2030. One of the programs carried out by the government in malaria control to achieve elimination is the mass distribution and use of insecticide-treated mosquito nets. The use of insecticide-treated mosquito nets is one of the efforts to reduce malaria cases through vector control. Insecticide mosquito nets are recommended as a strategic step to break the chain of malaria transmission because the insecticide content in the treated fibers can kill mosquitoes. The data used in this paper is data on the percentage of mosquito mortality from the efficacy test of insecticide-treated mosquito nets to see the killing power of mosquito nets which is then used to assess the effectiveness of mosquito nets in vector control. The data were obtained from scientific studies of articles published in scientific journals. From the data collected, it is known that some insecticide-treated mosquito nets used by the community are effective in vector control, but some are no longer effective. The best period for using mosquito nets is less than 6 months by paying attention to the proper washing method so that insecticide-treated mosquito nets are still effective.